PENGARUH PROFITABILITAS, LEVERAGE, KESEMPATAN INVESTASI, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Winnie Taurisia Pranata; Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research intends to determine the influence of profitability, leverage, company size, and investment opportunities on dividend policy in banking companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. This study used a sample of 31 data with a purposive sampling method. This study uses data processing techniques multiple regression analysis with the SPSS ver 26 application and Google Sheets in processing the data. The results show that leverage has a positive and significant effect on dividend policy. While profitability and investment opportunities do not have a positive effect on dividend policy. Firm size has no negative effect on dividend policy. The implication of this research is the need to increase the influence of profitability, leverage, investment opportunities, and company size on dividend policy so as to provide a good signal to investors.